Pregnancy clause in their paper marriage - Hewitt, Kate (Harlequin presents, 2024)
Three years of convenient marriage... Now the terms are changing... Christos Diakis has always remained an enigma to Lana. Even after she married him to escape a haunting past. But Lana has just discovered she's running out of time to have the future she wants. So she must ask the impossible of her purely on-paper husband... I want to have your baby. Honoring their strict agreement, Christos has fought hard to ignore the electricity that accompanies every choreographed public touch. Lana's request rocks the very foundations of their union. And Christos has neither the power -- nor wish -- to decline...